Case report: Plasma cell leukemia secondary to multiple myeloma successfully treated with anti-BCMA CAR-T cell therapy - Deng, Jingjing; Lin, Yuehui; Zhao, Defeng; Tong, Chunrong; Chang, Alex H.; Chen, Wenming; Gao, Wen (Frontiers in Oncology, 2022)
Chimeric antigen receptor (CAR)-T cell therapy provides an effective salvage treatment for relapsed/refractory multiple myeloma (RRMM) patients. End-stage RRMM with plasma cell leukemia (PCL) transformation is highly aggressive and resistant to conventional therapy. There is an urgent need for new therapeutics and CAR-T therapy may play an important role. We report a case of PCL secondary to RRMM successfully treated with CAR-T cell therapy targeting B-cell maturation antigen (BCMA). A woman was diagnosed as having MM 4 years ago and progressed to secondary PCL (sPCL) of five prior lines of treatment including proteasome inhibitors, an immunomodulatory agent, cytotoxic drugs, and an anti-CD38 monoclonal antibody. After receiving a BCMA CAR-T therapy, she achieved a stringent complete response that lasted 9 months. Then, the patient irregularly took venetoclax 10 mg per day due to a slightly higher λ FLC concentration, which did not meet the criteria for progression. She maintained a complete response for the following 7 months. In conclusion, BCMA CAR-T therapy may be a promising therapeutic approach in PCL patients. More studies are needed to evaluate the benefit of anti-BCMA CAR-T therapy in PCL patients. Clinical Trial Registration:www.chictr.org.cn, ChiCTR1900024388, Registered 9 July 2019.